The Effect of Global Monetary Policy Changes on the Financial Strategy of International Companies - Rumasukun, Mohammad Ridwan (Golden Ratio of Mapping Idea and Literature Format, 2024)
In the interconnected global economy, the financial strategies of international corporations play a crucial role in navigating the dynamic landscape shaped by various factors, including monetary policies set by central banks worldwide. This narrative explores the intricate interplay between global monetary policy changes and the financial strategies of multinational corporations, investigating how shifts in these policies reverberate across borders, impacting corporate decision-making, risk management, and performance. Over recent decades, significant transformations in monetary policy frameworks have occurred, driven by evolving economic paradigms, financial crises, and geopolitical dynamics. Central banks have deployed a range of tools, from conventional inflation targeting to unconventional measures like quantitative easing, to stabilize economies and stimulate growth. However, the effectiveness and unintended consequences of these policies transcend domestic boundaries, permeating the international financial system and shaping the strategic imperatives of multinational corporations. The impact of global monetary policy changes on international companies' financial strategies is substantial. U.S. monetary policy shocks notably affect foreign firms, especially those with extensive global production linkages and financial constraints. Financial globalization has made domestic financial conditions more vulnerable to external shocks, reinforcing the case for price stability as an optimal monetary rule. The volatility of foreign currency exchange rates significantly affects international budgeting, while multinationals with foreign involvement exhibit lower leverage ratios and rely more on short-term borrowing. One primary channel through which global monetary policy changes influence international companies is by altering financing costs and access to capital. Changes in interest rates and liquidity conditions affect borrowing costs for firms operating across borders, impacting investment decisions, capital allocation, and capital structure optimization. Additionally, these changes induce currency fluctuations and volatility, necessitating robust currency risk management strategies to safeguard revenues and mitigate exchange rate exposure. Furthermore, global monetary policy changes affect asset prices, financial markets, and investor sentiment, shaping the risk-return dynamics faced by international companies. Expansive monetary policies often fuel asset price inflation and influence investment strategies, while abrupt policy shifts can trigger market dislocations and liquidity constraints. Beyond financial markets, monetary policy changes influence macroeconomic variables, such as economic growth, inflation, and trade patterns, shaping international companies' operating environments and strategic decisions. In conclusion, the interconnectedness of global financial markets accentuates the importance of agility, flexibility, and strategic foresight for multinational corporations in navigating the impact of monetary policy changes on their financial strategies and overall performance.